MAGNETIC STUDIES OF SEDIMENTS AND SOILS AS A TOOL FOR DETECTION OF DANGEROUS GEODYNAMIC EXOGENIC PROCESSES ON THE EXAMPLE OF THE KHORTYSYA RESERVE - MENSHOV, Oleksandr; HOROSHKOVA, Lidiia; GOLUB, Alexander; HOROSHKOV, Stanislav (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. During the military activity, areas with different types of land use experience significant negative impacts. The natural and anthropogenic complexes of the Khortytsia Nature Reserve are under constant threat from missile strikes, drone attacks, guided aerial bombs, and other forms of military activity. Additional pressure is exerted by the urban environment and heavy industry of Zaporizhzhia. Moreover, the disappearance of the Kakhovka Reservoir has led to irreversible changes in biodiversity, water regimes, and landscape conditions in the surrounding areas, including Khortytsia Island. The aim of this study is to assess the changes in the natural and anthropogenic complexes of the Khortytsia Reserve by analyzing magnetic properties and determining the concentrations of hazardous chemical compounds, particularly heavy metals, in the bottom sediments of dried-up lakes formed after the destruction of the Kakhovka Dam, as well as in the soil.Methods. Magnetic susceptibility was measured using a laboratory KLY-2 Kappabridge. Mass-specific magnetic susceptibility (χ) was determined by normalization to mass. The content of chemical elements was analyzed by X-ray fluorescence (XRF) analysis using Elvatech equipment.Results. The study considers the bottom sediments of Lake Kamyane, Prohniy, Rysove, and Pishchane, as well as the soil of the forested area. High magnetic susceptibility was detected. Most observation points recorded relatively high values of χ=50–100×10-8 m³/kg, while some samples exhibited even more extreme values (χ=100–300×10-8 m³/kg). These elevated values may be associated with either anthropogenic pollution or the lithogenic origin of magnetic minerals transported from crystalline basement outcrops in the vicinity of Khortytsia. Additionally, increased magnetic susceptibility was observed in the sandy soils of the mixed forest. A significant correlation with magnetic susceptibility was found only for chromium (correlation coefficient is 0.4). At the same time, exceedances of the maximum allowable concentrations of heavy metals were recorded: lead by 2–8 times, zinc by 2–10 times, chromium by 20–50 times, copper by 10–20 times, nickel by 5–20 times, and cobalt by 5–8 times.Conclusions. The magnetic susceptibility of the bottom sediments of lakes and the soil of Khortytsia Island is high. It is assumed that this is due to the accumulation of lithogenic material from the weathering of crystalline basement rocks. The concentration of a number of elements, primarily heavy metals, exceeds the MPC by 2–50 times. However, a significant correlation coefficient was recorded only between χ and Cr (0.4). Therefore, magnetic minerals do not have a genetic connection with materials containing heavy metals. That is, most likely there is no anthropogenic impact.
Keywords: sediments; soil; heavy metals; pollution; magnetic susceptibility